Reworking Class - Hall, John R. (Book collections on Project MUSE., 1997)
The twelve essays in this volume propose new directions in the analysis of class. John R. Hall argues that recent historical and intellectual developments require reworking basic assumptions about classes and their dynamics. The approaches developed by the contributors effectively abandon the notion of a transcendent class struggle. They seek instead to understand the historically contingent ways in which economic interests are pursued under institutionally, socially, and culturally structured circumstances. In his introduction, Hall proposes a neo-Weberian venue intended to bring the most promising contemporary approaches to class analysis into productive exchange with one another. The chapters that follow address a wide range of issues concerning class.